Impact of ecological UV radiation on the photochemistry of nuclear DNA - Sánchez, Ana G.; Gabrielli, Adriana; Keszenman, Deborah J. (Biophysical reviews, 2025)
Solar radiation is predominantly Earth’s natural ultraviolet (UV) radiation source. The biological effects of UV radiation have been the subject of scientific interest for decades. The most frequent and abundant types of DNA damage comprise the formation of cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6-4) pyrimidone (6-4PP) photoproducts. Upon UVA excitation, the 6-4PPs may undergo an intramolecular 4 π electrocyclization of the pyrimidone ring, arising photolesions known as Dewar isomers. The photochemistry pathways of UVA/UVB-induced DNA damage are discussed. Photosensitization-mediated reactions have traditionally been categorized as either oxygen-independent or oxygen-dependent. In oxygen-independent processes, the underlying mechanism involves triplet-triplet energy transfer. Among the reactive oxygen species (ROS) generated by UV radiation ( 1 O 2 , O 2 •− , • OH, H₂O₂), singlet oxygen ( 1 O₂) is highly reactive and a primary contributor to oxidative DNA damage in cells and human skin following UVA exposure, as observed in the production of 8-oxoguanine (8-OxoG). The exposure of melanocytes to UV radiation upregulates nitric oxide synthase (NOS) and NADPH oxidase (NOX), producing nitric oxide and superoxide, which recombine to produce peroxynitrite. This highly oxidizing species is responsible for melanin chemiexcitation, producing carbonyl products that transfer energy to the DNA molecule to produce CPDs in the dark several hours after UV exposure ends. The peroxynitrite generated could also lead to other types of DNA damage, such as the formation of 8-nitroguanine (8-NitroG), which requires further study.